Effects of Monetary Policy in Romania - a Var Approach - Iulian Popescu (CES Working Papers, 2012)
Understanding how monetary policy decisions affect inflation and other economic variables is particularly important. In this paper we consider the implications of monetary policy under the inflation targeting regime in Romania, based on an autoregressive vector method including recursive VAR and structural VAR (SVAR). Therefore, we focus on assessing the extent and persistence of monetary policy effects on gross domestic product (GDP), price level, extended monetary aggregate (M3) and exchange rate. The main results of VAR analysis reflect a negative response of consumer price index (CPI), GDP and M3 and positive nominal exchange rate behaviour to a monetary policy shock, and also a limited impact of a short-term interest rate shock in explaining the consumer prices, production and exchange rate fluctuations.
Keywords: E31; E52; E58; C32; 330; monetary policy; transmission mechanism; vector auto regressions Romania